Development of a Portable Process Data Acquisition System - Nils Heinrich (2010)
The advantage of recording process data stems from its ability to create a basis for the finding of saving potentials and the valuation of optimization measures. For that reason system solution offering the acquisition of different data sources becomes more important. This project discusses with a design focusing the creation of a portabel intregrated system solution.